2009
DOI: 10.1093/eurjhf/hfp156
|View full text |Cite
|
Sign up to set email alerts
|

Food‐restriction in obese dyslipidaemic diabetic mice partially restores basal contractility but not contractile reserve

Abstract: AimsWeight reduction programmes in morbidly obese, diabetic, and hyperlipidaemic subjects usually improve cardiac load and subsequently reverse hypertrophy. However, their effect on contractile dysfunction and impaired cardiac functional reserve is unknown. Methods and resultsThe effect of food-restriction-induced weight loss on in vivo cardiac contractility before and during beta-adrenergic stimulation was assessed using left ventricular pressure-volume analysis in a mouse model featuring obesity and Type II … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 32 publications
3
12
0
Order By: Relevance
“…Furthermore, these cellular defects are in parallel with previous in vivo studies in our laboratory and with clinical studies [1,2,6-8]. …”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Furthermore, these cellular defects are in parallel with previous in vivo studies in our laboratory and with clinical studies [1,2,6-8]. …”
Section: Discussionsupporting
confidence: 80%
“…All together, our data provide evidence for contribution of intrinsic cellular mechanisms, in recovering diastolic function after diet and ACE-I, associated with extrinsic mechanisms (eg. reduced ventricular-vascular stiffening, reduced subendothelial lipid deposition and increased endothelium-dependent relaxation) [6-11,19]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely accepted that the systolic dysfunction which might occurred in the middle or late stage of diabetic cardiomyopathy is associated with apoptosis and fibrosis. On the other hand, many studies have reported that compared with wild type mice, db/db mice may exhibit no significant fibrosis at 12, 24, and 36 weeks old [58, 59]. In this study, systolic dysfunction and cardiac fibrosis of db/db mice were not observed, which matched with the early phase of diabetic cardiomyopathy, represented by diastolic dysfunction only.…”
Section: Discussionsupporting
confidence: 60%
“…However, many of the obesity studies have been conducted in genetic animal models, 11,12 which may not reflect most of human obesity causes. Thus, in the present study, we tested whether 10 weeks of exercise training and/or caloric restriction would improve cardiac function in obese rats fed with a high-fat and sucrose diet that mimics food habits of humans living in Western countries.…”
mentioning
confidence: 99%